(untitled) (Journal of the Asiatic Society of Bangladesh, Humanities, 2023)
This paper proposes a process of synthesis based on Chinese socio-historical context in order to gain a more comprehensive understanding of the synthesis of three major religious traditions of East Asia such as Confucianism, Taoism and Buddhism. At the same time, to be considered is the syncretic approach through which these religions have attained popularity throughout all Eastern and Far Eastern parts of Asia. Thus, in order to make a reasonable justification for the current study, an attempt is made to explore how these religions have appeared to be more or less similar to each other in case of their beliefs and practices. The purpose of the current paper is to decipher the points where and how these three religions interact with each other in terms of belief and practice that is based on a cultural bridge between China and other East Asian countries. This paper offers an overview of the harmonious synthesis of Taoism, Confucianism and Buddhism in the matrix of Chinese culture. In conclusion, it points out a new mode of syncretism which can be called "Hybridization"- a new insight into the process of synthesis. Journal of the Asiatic Society of Bangladesh (Hum.), Vol. 68(2), 2023, pp. 207-218